Comparative Analysis of Artificial Intelligence Technologies Based on Scope for the Production of Research Texts (Praxis Educativa, 2025)
This article presents a descriptive exploratory study that comparatively examines artificial intelligence (AI) technologies to identify the most relevant ones for the production of scientific texts, particularly for exploratory and communicative reading and writing. To achieve this, the research is conducted in three phases from August to December 2024: (1) survey and selection of tools; (2) in-depth analysis of applications considering categories such as functionality, security, and user experience; and (3) classification and systematization of AI technologies. As a result, the tools were classified into two dimensions: (1) their contribution to the reading and writing process (exploratory and communicative); and (2) the range of functionalities of the tool (multiple tasks or specific tasks). The conclusions systematize the theoretical and methodological contributions of the study, highlighting the established distinction of AI technologies according to their scope for different types of reading and writing carried out during research processes.
Keywords: artificial intelligence, research strategies, academic reading, academic writing, revision.